B7-H1 Expression Is Required for Human Endometrial Regenerative Cells in the Prevention of Transplant Vasculopathy in Mice - Kui Ye; Xu Lan; Grace Wang; Baoren Zhang; Xiaoxi Xu; Xiang Li; Yiming Zhao; Hao Wang (Stem Cells International)
Vasculopathy is one of the primary pathological changes in chronic rejection of vascularized allograft transplantation. Endometrial regenerative cells (ERCs) are mesenchymal-like stromal cells with immunosuppressive effect. B7-H1 is a negative costimulator that mediates active immune suppression. The aim of this study was to investigate the requirement of B7-H1 in the immunoregulation of ERCs in preventing transplant vasculopathy of aorta allografts. The results showed that B7-H1 expression on ERCs was upregulated by IFN-γ in a dose-dependent manner and it was required for ERCs to inhibit the proliferation of peripheral blood mononuclear cells (PBMCs) in vitro. ERCs could alleviate transplant vasculopathy, as the intimal growth of transplanted aorta was limited, and the preventive effects were correlated with an increase in the percentages of CD11c+MHC class IIlowCD86low dendritic cells, CD68+CD206+ macrophages, and CD4+CD25+Foxp3+ T cells, as well as a decrease in the percentages of CD68+ macrophages, CD3+CD4+ T cells, CD3+CD8+ T cells, and donor-reactive IgM and IgG antibodies. Moreover, overexpression of B7-H1 by IFN-γ can promote the immunosuppressive effect of ERCs. These results suggest that overexpression of B7-H1 stimulated by IFN-γ is required for ERCs to prevent the transplant vasculopathy, and this study provides a theoretical basis for the future clinical use of human ERCs.